Respuesta :
[tex]\sqrt[3]{27a^3b^7}\\\\\text{use}\ \sqrt[3]{xy}=\sqrt[3]{x}\cdot\sqrt[3]{y}\\\\=\sqrt[3]{27}\cdot\sqrt[3]{a^3}\cdot\sqrt[3]{b^7}=\sqrt[3]{3^3}\cdot\sqrt{a^3}\cdot\sqrt[3]{b^{3+3+1}}\\\\\text{use}\ \sqrt[3]{x^3}=x\ \text{and}\ a^n\cdot a^m=a^{n+m}\\\\=3\cdot a\cdot\sqrt[3]{b^3\cdot b^3\cdot b^1}\\\\\text{use}\ \sqrt[3]{xy}=\sqrt[3]{x}\cdot\sqrt[3]{y}\\\\=3a\cdot\sqrt[3]{b^3}\cdot\sqrt[3]{b^3}\cdot\sqrt[3]{b}\\\\\text{use}\ \sqrt[3]{x^3}=x\\\\=3a\cdot b\cdot b\cdot\sqrt[3]{b}=\boxed{3ab^2\sqrt[3]{b}}[/tex]
Answer:
The simplest form is [tex]3ab^2\sqrt[3]{b}[/tex]
Step-by-step explanation:
Here, the given expression is,
[tex]\sqrt[3]{27a^3b^7}[/tex]
[tex]=(27a^3b^7)^\frac{1}{3}[/tex] ( [tex]\sqrt[n]{x} = x^\frac{1}{n}[/tex] )
[tex]=(27a^3b^{6+1})^\frac{1}{3}[/tex]
[tex]=(3^3a^3b^6.b^1)^\frac{1}{3}[/tex] ( [tex]a^{m+n}=a^m.a^n[/tex] )
[tex]=((3ab^2)^3)^\frac{1}{3}.b^\frac{1}{3}[/tex] ( [tex]a^m.b^m=(ab)^m[/tex] )
[tex]=3ab^2.\sqrt[3]{b}[/tex] ( [tex](a^m)^n= a^{mn}[/tex] )